100 Years After Cours de Linguistique Générale: The Emergency of Pragmatic Linguistics (Palimpsesto, 2019)
The purpose of this article is to present an overview of current trends in linguistics. Given the complexity involved in this work, it is assumed that functionalist research programs, focused on the use and functions of language, are the most innovative in the field and are in tune with the pragmatic turn in cognitive sciences, and they even generate the conditions for a new pragmatic linguistics in which actions and interaction are understood as constitutive of cognitive systems. It starts with an analysis of Saussure's approaches and the structuralist program, with the aim that their approaches should serve as a background and allow comparison with three programs that conceive language as something dynamic connected constitutively with human experience: grammaticalization, linguistic typology, and cognitive linguistics. It is concluded that linguistic research advances in a different sense to that advocated by structuralism, since the new currents seek to characterize the way in which patterns and linguistic regularities emerge, are processed, are transformed, and vary in use.
Keywords: Linguistic functionalism; pragmatic turn; grammaticalization; linguistic typology; cognitive linguistics; pragmatic linguistics